Molecular analysis of germline t(3;6) and t(3;12) associated with conventional renal cell carcinomas indicates their rate-limiting role and supports the three-hit model of carcinogenesis - Yusenko, Maria; Nagy, Anetta; Kovacs, Gyula (Cancer genetics and cytogenetics, 2010)
We describe the molecular analysis of chromosomal rearrangements in familial t(3;6)(p12.3;q24.3) and t(3;12)(q13.13;q24.23) associated with the development of conventional renal cell carcinomas (RCC). We mapped the breakpoints by high-density oligo array comparative genomic hybridization of tumor cells in t(3;6) at chromosome 3p12.3 between PDZRN3 and CNTN3; the chromosomal rearrangement at 6q24.3 was mapped within the seventh intron of the STXBP5 gene. In the second case, the break at 3q13.13 was mapped downstream of PVRL3 and the breakpoint at 12q24.23 between HSPB8 and CCDC60, one allele of the latter being deleted. Reverse transcriptase polymerase chain reaction analysis of the PDZRN3, CNTN3, STXBP5, PVRL3, HSPB8, and CCDC60 genes revealed slight variation in the copy number of transcripts, but without correlation to the chromosomal rearrangements in translocation-associated and sporadic conventional RCCs. Loss of heterozygosity at chromosome 3p and mutation of VHL occurred at the same frequency in both familial and sporadic cases. Based on our model of nonhomologous chromatid exchange and the data on molecular studies, we suggest that the germline translocation serves as a rate-limiting step toward tumor development by generating a high number of cells with loss of the derivative chromosome carrying the 3p segment.